The usefulness of cost information: a cross cultural study between Brazilian and British hospitals - Gonçalves, Márcio Augusto; Alemão, Márcia Mascarenhas; dos Santos, Lucas Maia (Anais do Congresso Brasileiro de Custos - ABC)
This study was carried out to investigate different modes of governance within Brazilian and British hospitals and the usefulness of cost information in terms of managerial plannig and control. The research was conducted by cross cultural analysis, using several statistical methods for measuring organisation characteristics, seeking to gain a deeper understanding of the profile of both hospitals and respondents. This study showed the dominance of hierarchy and clan as being the most relevant modes of governance in Brazilian and British hospitals. This discussion is relevant considering the congruence level of goals and the ambiguity level of performance measurement. Also, it defines which form of governance is more predominant. The exploratory and quantitative survey methods were used to test the research questions. After conducting a survey using a structured questionnaire, semi-structured interviews with middle managers at chosen case study hospitals were undertaken. In the cases analyzed, it was possible to identify a significant difference between the use of cost information in hospitals, allowing inferences between different modes of governance. The lack of studies about the use of cost information in planning and control regarding public hospitals impedes any other comparison or assessment considering empirical data. One of the objectives of this paper was to generate initial material for future researchers. Besides, the knowledge about the current scenario of the usefulness of cost information mainly in planning and control is relevant when associated with modes of governance.